Use of Alcohol, Tobacco, and Caffeine and Suicide Attempts: Findings From a Nationally Representative Cross-sectional Study. (March 2020) - Cho, Myong Sun
In this study, the association between students' substance use and suicide attempts in the past 1 year was examined using secondary data from the 13th Korea Risk Behavior Web-based Survey. Participants were 7th- to 12th-grade students and 50.9% were male. A binominal logistic regression analysis was used to investigate the association between past experience of substance use (alcohol, tobacco, and caffeine) and suicide attempts after controlling for sociodemographic and psychological factors. Compared with no use, daily use of alcohol (odds ratio [OR] = 8.00), caffeine (OR = 2.13), and tobacco (OR = 1.41) was associated with increased odds of suicide attempts. These results indicate that school-based suicide prevention programs should cover awareness, surveillance, and treatment referral for these 3 substances. Moreover, mental health professionals should monitor intake of these substances when evaluating risk of suicide attempts in youth.